The effect of the recent insider-trading scandal on stock prices of securities firms - Torabzadeh, Khalil M. (Journal of business ethics, 1989)
This paper addresses the impact of the unethical business conduct of a few individuals that shook the financial market in 1986. Specifically, in the study undertaken for this paper, the wealth status of the shareholders of securities firms was examined in relation to the public disclosure of the insider-trading scandals involving Dennis Levine, Ivan Boesky, and their confederates. It was hypothesized that the expected market-adjusted stock returns for the securities firms would be negative as a result of the scandals. The findings of the study supported the hypothesis.